Effects of vegetation restoration types on soil nutrients and soil erodibility regulated by slope positions on the Loess Plateau - Dong, Lingbo; Li, Jiwei; Zhang, Yu; Bing, Mengyao; Liu, Yulin; Wu, Jianzhao; Hai, Xuying; Li, Ao; Wang, Kaibo; Wu, Puxia; Shangguan, Zhouping; Deng, Lei (Journal of environmental management, 2022)
Soil degradation is significantly increased driven by soil nutrient loss and soil erodibility, thus, hampering the sustainable development of the ecological environment and agricultural production. Vegetation restoration has been widely adopted to prevent soil degradation given its role in improving soil nutrients and soil erodibility. However, it is unclear which vegetation type has the best improving capacity from soil nutrient and soil erodibility perspectives. This study selected three vegetation restoration types of grasslands (GL), shrublands (SL), and forestlands (FL) along the five slope positions (i.e., top, upper, middle, lower, and foot slope), to investigate the effects of vegetation restoration types on soil nutrients and soil erodibility. All vegetation restoration types were restored for 20 years from croplands (CL). We used comprehensive soil nutrient index (CSNI) and comprehensive soil erodibility index (CSEI) formed by a weighted summation method to reflect the effect of vegetation restoration on the improving capacity of soil nutrient and erodibility. The results showed the vegetation types with the highest comprehensive soil quality index (CSQI) at the top, upper, middle, lower and foot slope were FL (1.92), FL (1.98), SL (2.15), FL (2.37) and GL (3.93), respectively. When only one vegetation type was considered on the entire slope, SL (0.59) and FL (0.59) had the highest CSNI, the SL had the lowest CSEI (0.34) and the highest CSQI (1.89). The CSNI was mainly influenced by soil structure stability index (SSSI), sand content, silt + clay particles, and CSEI was controlled by soil organic matter (SOM), macroaggregates and microaggregates. Moreover, the CSQI was influenced by pH, silt and clay content, and biome coverage (BC). The study suggested the SL were advised as the best vegetation restoration type on the whole slope from improving soil nutrients and soil erodibility. •Vegetation type, slope position and their interaction affected on soil quality.•Soil nutrients strongly affected on the variations of soil erodibility.•Shrublands had the best positive effect on soil quality on the whole slope.